P307 The use of the patient safety form in patients with inflammatory bowel disease, can improve the low screening and starting HBV prophylaxis rates in real life. (25th January 2019) - Demir, M; Uçar, E; Çelik, M M
Abstract: Background: The rate of hepatitis B virus(HBV) screening and starting HBV prophylaxis is low in patients with immunosuppressive therapy in daily practice. While starting the biological therapies in the patients with inflammatory bowel disease (IBD), use the patient safety form is mandatory in Turkey but there is no such requirement for long-term high-dose steroids. The aim of this study was to determine how much HBV screening and rates of antiviral treatment applied in patients with IBD in daily practice and to evaluate the relationship between the patient safety form and rate of HBV screening and starting HBV prophylaxis. Methods: This is a retrospective study. Between January 2010 and May 2018, patients who received biological agents (including adalimumab, certolizumab, infliximab, and vedolizumab) with/without steroids, 5-aminosalicylic acid and/or immunomodulators (Group 1; use the patient safety form mandatory) and long-term high-dose steroids with/without 5-aminosalicylic acid and/or immunomodulators (Group 2: use the patient safety form not mandatory) in Medical University of Mustafa Kemal were included in the study. HbsAg and Anti-HbcIg tests performed during the period up to 1 year before treatment of immunosuppressive agent were accepted as screening. Methylprednisolone or equivalent steroid of its use for at least 4 weeks and at least 10 mg/day were considered to be as long-term high-dose. HbsAg and/or HbcIg positivity was defined as a risky patients for starting antiviral prophylaxis. Results: A total of 1012 patients were included in the study. The immunosuppressive treatment distributions of the patients were as follows; 183 biological agents(Group 1), 829 long-term high-dose steroids (Group 2). Seven hundred and sixteen (70.7%) of the patients had screened for HbsAg and/or anti-HBcIg. HbsAg and anti-HBcIgG screening were found in 40.2% (407/1012) patients and only HBsAg screening was found in 30.5 (309/1012) patients. HbsAg positivity was found in 5.4% (39/716) of patients and HbsAg negative and anti-HBcIg positivity in 30.7% (125/407) of patients. The rates of HBsAg and/or anti-HBcIg screening were 95.6% (175/183) in group 1 and 65.2 (541/829) in group 2 ( p < 0.001). Rates riskly patients for starting antiviral prophylaxis were found in % 21.7 (38/175) in Group 1 and %23.2 (126/541) in Group 2 ( p > 0.05). Rates starting HBV prophylaxis were %100 (38/38) in Group 1 and %56.3 (71/126) in Group 2 ( p < 0.001). Conclusions: The scanning rates are low in patients with IBD receiving long-term high-dose steroids and it was found that only half of risky patients received antiviral treatment. We also believe that the use of the patient safety form application in patients with IBD receiving long-term high-dose steroids can improve the low screening and treatment rates in real life.